Jaguar Dealership - Enrique Norten (Oz, 2000)
Visibility from the distant road was the main charge of the Jaguar dealership, located on the sparsely developed edge of Mexico City where upscale office parks and shopping malls are just beginning to cluster around newly paved expressways. We gave the building a clearly legible form, stacking two strongly geometric boxes one upon the other: a gleaming, four-story tall vertical balances precariously on a dark, low-lying horizontal.